Application of TPS (Think Pair Share) Type of Cooperative Learning Model to Improve Activities and Learning Outcomes of X IPA1 Students in the Material of Inverse Function at SMA Negeri 3 Jember Academic Year of 2016/2017 - Teripena E. C (Pancaran Pendidikan, 2018)
Mathematics is a school subject that has abstract objects and is built based on the process of deductive reasoning. It is the concept of truth that is got as the logic result from the truth before. Mathematics approach learning is easy to be understood by students. The process of deductive reasoning is used for students to practice ways of systematic, logical, creative and consistent thinking. The problems of this research are: (a) How do teachers increase the students' learning outcomes by the application of TPS type of cooperative learning method? (b) What are the effects of TPS type of cooperative learning model on students' learning motivation? The purposes of this research are: (a) to know whether there is an increase in student learning achievement after the TPS cooperative learning model is applied. (b) to know the effects of students’ learning motivation after the TPS cooperative learning model is applied. The research uses action research with three cycles. Every cycle consists of four steps, namely planning, observation, reflection an revision. The study target is the students of X IPA1 of SMAN 3 Jember. The data is gained from the result of the formative test and teaching-learning observation sheet. The result of the research is that the student's achievement increases from the first cycle up to the second, namely 45.16% in the first cycle with 17 students not completing the learning and 83.87% with 5 students not completing the learning in the second cycle. The research conclusion is that TPS cooperative learning model can affect positively to students’ learning motivation to understand the material concepts so the students can reach the maximum achievement and that this learning model can be used as one of mathematics learning alternatives